(untitled) (Asean Journal of Engineering Education, 2024)
Brian R. Belland’s Instructional Scaffolding in STEM Education: Strategies and Efficacy Evidence provides an in-depth analysis of instructional scaffolding’s role in enhancing student learning within STEM disciplines. The book focuses on the efficacy of computer-based scaffolding, exploring its potential to support students engaged in problem-centered instructional approaches such as project-based and inquiry-based learning. Belland meticulously reviews the theoretical foundations of scaffolding and presents findings from a meta-analysis of 144 studies, identifying scaffolding strategies that most effectively promote higher-order thinking, problem-solving, and deep content knowledge. The book also addresses the customization of scaffolding, stressing the importance of adapting support to meet individual learner needs. Key themes include the integration of conceptual, strategic, and motivational scaffolding, as well as their impact on cognitive outcomes. This review highlights the book’s relevance to educators, researchers, and curriculum developers, offering practical insights for integrating scaffolding into STEM education to foster more engaged and capable learners.